Pengaruh Video Edukasi Hypnobirthing untuk Mengatasi Tokophobia pada Wanita Usia Produktif - Desy Winda; Anggy Trisnadoli; Mita Fani Tri Mutya (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Pregnancy is a time awaited by many women. Entering pregnancy, there are many changes that occur both biologically due to hormonal changes, but also psychologically. Pregnancy generally occurs at a productive age before entering menopause. Pregnancy is a difficult phase, so many pregnant women experience excessive fear and anxiety during pregnancy and childbirth, due to many factors, both internal and external. Fear and anxiety are usually more felt in pregnant women with their first child, but in subsequent pregnancies there are still many who experience fear and anxiety. This is very bad if not handled properly, because it can endanger the condition of pregnant women and also their womb. Tokophobia is a common condition characterized by fear experienced by women in relation to the processes of pregnancy and childbirth. Various stakeholders, including healthcare professionals, psychologists, media outlets, and specialized teams, have sought solutions to address tokophobia. One popular approach is hypnotherapy, particularly hypnobirthing, which supports the processes of pregnancy and childbirth. Hypnobirthing involves the utilization of positive suggestions to facilitate and ease the process of childbirth while reducing potential fears experienced by the mother. Educational videos are frequently employed within hypnobirthing, combining auditory and visual elements to provide positive benefits to viewers. Based on research and testing conducted on 15 productive age pregnant women with tokophobia in Pekanbaru, the use of educational hypnobirthing videos has proven to have a positive impact in reducing levels of fear throughout the pregnancy process.